Synthesis of Some 2-Thioxo-imidazolidin-4-one Derivatives and its Antimicrobial Activity - A. Jamal Abdul Nasser; A. Idhayadhulla; R. Surendra Kumar; J. Selvin (E-Journal of Chemistry)
Series of newly prepared 3-{[2,6-bis(4-substituted phenyl)-1- methylpiperidin-4- ylidene] amino}- 2-thioxo-imidazolidin-4-one derivatives (3a-3f) have been synthesized by the cyclization of compound (2a-2f), ethyl chloro acetate and fused sodium acetate. The chemical structures were confirmed by IR, 1H NMR and elemental analysis. The synthesized compounds were screened for their antimicrobial activity against four antibacterial and four antifungal organisms.